Unplanned surgery increases the morbidity of patients with solitary plasmacytoma of femoral bone: a case report - Wiratnaya, I. Gde Eka; Arimbawa, Ida Bagus Gede; Sidharta, I. Made Tusan (International Journal of Research in Medical Sciences, 2018)
Solitary skeletal plasmacytoma is a malignant plasma cell tumour that accounts for 3-5% of all monoclonal gammopathies. Lytic bone disease is a hallmark, and a substantial percentage of patients develop pathologic fractures. For lesions involving the femur, internal fixation frequently fails; therefore, prosthetic reconstruction may be the optimal choice for treatment. A 52-year-old male patient with pathological fracture of right femoral bone. Patient was undergone surgery with internal fixation. The pain had been continuing for several months and giant masses has developed on affected side. Further test was done and showed solitary plasmacytoma of proximal femur. The patient was treated with cemented modular prosthesis following tumor excision. Treatment of pathological fracture often challenging. Unplanned surgery could be devastating for the patient. Compare to internal fixation, cemented modular prosthesis is designed as a modular system that can be used to replace diseased or deficient bone in the femur following wide excision. Treatment of pathological fractures in solitary plasmacytoma with modular prosthesis appears to be a feasible option. They were able to mobilize early with good pain relief and had a useful functional limb. Further diagnostic test should be done for fracture of proximal femoral bone that considered pathologic. Limb salvage surgery with modular prosthesis can be considered as a viable option for treating painful pathological fractures in solitary plasmacytoma. It provides pain relief, early mobilization, and good functional outcome with improved quality of life.